BUILDING HARMONY: STRATEGIES AGAINST RELIGIOUS INTOLERANCE FOR NATIONAL UNITY - Alam, Suluh Mardika; Basri, Hasan; Syafi'i, Imam (JURNAL SETIA PANCASILA, 2024)
The term harmony is synonymous with the term tolerance. Harmony is a term filled with good and peaceful meaning content. The point is to live together in society with unity of heart and agree not to create disputes and quarrels. Living in harmony is everyone's dream. Differences on the one hand can be a strength if managed well and professionally. However, if not, differences in worldviews between countries, will become a factor of national disintegration and prolonged conflict. This article aims to find out how strategies to fight religious intolerance in Indonesia. The method used in this research is library research, which traces books and findings from interfaith harmony studies. The results of this study explain that there are 6 strategies that can be done in building inter-religious harmony, namely internalizing tolerance, maintaining kinship (ukhuwah), respecting and appreciating each other, trusting each other and avoiding prejudice, clarifying and confirming information obtained and acting fairly.